Effects of various TiO2 nanostructures and graphene oxide on photocatalytic activity of TiO2 - Gao, Peng (2014)
The nanostructures of TiO2 significantly affect its photocatalytic activity. In this work, various TiO2 nanostructures have been successfully synthesized, including one-dimensional (1D) TiO2 nanotube, 1D TiO2 nanowire, three-dimensional (3D) TiO2 sphere assembled by nanoparticles (TiO2 sphere-P) and 3D TiO2 sphere assembled by nanosheets (TiO2 sphere-S). The results of photodegradation activity towards acid orange 7 (AO7) indicate that the photodegradation efficiency of TiO2 sphere-S is the highest among the investigated TiO2 nanostructures, even though the specific surface area of TiO2 sphere-S is lower than that of TiO2 nanotube. The best photodegradation activity of TiO2 sphere-S can be attributed to the highest light harvesting capacity resulted from multiple reflections of light, and hierarchical mesoporous structure. In addition, the combination of TiO2 sphere-S with graphene oxide (GO) sheets can further enhance the photodegradation efficiency of AO7 and disinfection activity of Escherichia coli (E. coli) under solar light, which is more energy efficient. The promising photocatalytic activity of GO-TiO2 composites is originated from the enhanced light absorption and efficient charge separation. Hence, this study paves a way for improving the performance of other photocatalysts.